Peran Divisi Keimigrasian Kemenkumham Kalsel dalam Penyebaran Informasi Keimigrasian dan Paspor Elektronik - Norhaifa; Annida Fitri; Izhar; Hanif Deedat Syaifullah; Muhammad Rizky Fatur Alauddin; Jalaluddin (Interdisciplinary Explorations in Research Journal, 2024)
This research aims to analyze the role of the Immigration Division of the South Kalimantan Ministry of Law and Human Rights in disseminating information related to immigration, including the implementation of electronic passports. The main focus is the Immigration Goes to Campus program carried out at Lambung Mangkurat University (ULM) Banjarmasin. The research uses a qualitative descriptive approach, with data obtained through observation and documentation. The research results show that this program effectively increases students' immigration literacy, especially regarding the benefits of electronic passports.